The Effect of Using Turmeric as a Marinating Material on the Quality of Smoked Scad Fish (Decapterus macrosoma) - Nur Saleh; Asnani Asnani; Laode Muhamad Hazairin Nadia (Jurnal Fish Protech, 2023)
This study aims to determine the effect of using turmeric as a marinade on sensory values, TVB and proximate composition of smoked flying fish. The experimental design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 3 replications each, the treatments were A (control or 0% turmeric concentration), B (5% turmeric concentration), C ( turmeric concentration 10%) and D (turmeric concentration 15%). Data were analyzed using the analysis of variance (ANOVA) and the Duncan Multiple Range Test (DMRT) at the 95% level of confidence. Parameters observed were sensory analysis (appearance, smell, taste and texture), total volatile base (TVB) and proximate analysis (moisture content and protein content). The results of the study using turmeric as a marinade for smoked flying fish were significantly different in terms of appearance and taste (P<0.05), but the smell and texture were not significantly different (P>0.05). The selected treatment was treatment D (turmeric concentration 15%) with the average values of appearance, smell, taste and texture of 8.8, 7.8, 8.2 and 8.0 respectively. The use of turmeric in smoked flying fish did not have a significantly different effect on TVB, protein and water content (P>0.05). The TVB value of treatment D (selected treatment with 15% turmeric concentration) was 4.48 mg N/100 g which had a lower TVB value compared to smoked flying fish treatment A (control or 0% turmeric concentration) namely 9.80 mg N/ 100 gr and still suitable for consumption with a TVB value of 4.48 mg N/100 g. The water content value of smoked flying fish treatment D, namely 51.77%, had a lower water content value compared to treatment A, which was 52.32%, while the protein content showed that treatment D, which was 41.15%, had a higher protein content value than treatment A is 40.23%.